2017
DOI: 10.1001/jamafacial.2017.0060
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diet With Skin Histological Features in UV-B–Exposed Mice

Abstract: IMPORTANCE Long-term exposure to solar radiation produces deleterious photoaging of the skin. It is not known if diet can influence skin photoaging.OBJECTIVES To study the influence of a calorie-restricted diet and an obesity diet in mice exposed to long-term UV-B irradiation to assess if there is an association between diet and histopathological response to UV-B irradiation. DESIGN, SETTING, AND PARTICIPANTSIn this animal model study in an academic setting, the dorsal skin of SKH1 hairless mice receiving norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Caloric restriction with fasting has demonstrated improvement in multiple skin properties, including skin barrier function in both mice and humans [25]. Studies have also suggested that caloric restriction may improve the appearance of wrinkles and decrease the presence of oxidative stress [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Caloric restriction with fasting has demonstrated improvement in multiple skin properties, including skin barrier function in both mice and humans [25]. Studies have also suggested that caloric restriction may improve the appearance of wrinkles and decrease the presence of oxidative stress [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The mouse skin light model plays a crucial role in exploring skin inflammation, neoplastic lesions, immune response, and other related factors. [110,[113][114][115] This model has found extensive applications in life sciences, medical research, beauty, and other domains.…”
Section: Molecular Mechanisms Of Light Affecting Human Healthmentioning
confidence: 99%
“…Acute and chronic exposure to UV radiation has several effects on skin structure, promoting numerous histological changes, such as epidermal thickening, significant difference from nonirradiated and untreated group (NC); #P < 0.05: significant difference from irradiated and untreated group (IC). F1C, formulation control group (UVB-irradiated and treated with F1, i.e., emulsion without EAF); F2T, F2-treated group (UVB-irradiated and treated with F2; i.e., emulsion that contained 1% EAF) sunburn cell formation, dermal alterations (e.g., collagen degradation) and mast cell activation (49,50). Studies have shown that topical treatment with formulations that contain plant materials rich in phenolic compounds (e.g., ethanolic extract from Eucalyptus globulus leaves and ethyl acetate fraction from N. cuspidata leaves) decreased collagen degradation, in addition to inhibiting the formation of sunburn cells, inhibiting the increase in epidermal thickness and inhibiting the activation of mast cells in UVB-irradiated skin in mice (36,51).…”
Section: In Vivo Photochemoprotective Effects Of Topical Emulsion That Contained the Eaf Against Uvb-induced Inflammation And Oxidative Smentioning
confidence: 99%